PERAN PEMERINTAH DESA DALAM PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI HOME INDUSTRI KRIPIK PISANG DI DESA BANJAR KECAMATAN LICIN KABUPATEN BANYUWANGI - Afrida Nur Laili; Boni Irwanto (Department of Islamic Community Development, Faculty of Dakwah,Universitas Islam Ibrahimy Banyuwangi, 2022)
The problem of this research is the economic problems owned by the community and the realization of the government's function in community economic empowerment. So that the object of study from this study is the Role of the Village Government in Community Economic Empowerment through the Home Industry of Banana Chips in Banjar Village, Licin District, Banyuwangi Regency. The research used is qualitative. The analysis method is descriptive qualitative. Data collection techniques use interviews, observations and documentation. The result of this study is that the Banjar Village Government has implemented its work program well in terms of community empowerment. In terms of economic empowerment, the village government has succeeded in improving the community's economy through the banana chip home industry and has its own branding. But in terms of economic empowerment of this community, of course, it has encountered some obstacles. The obstacles experienced by the village government are limited funds from the government and the lack of maximum marketing made by the village government. Then the success achieved by the village government is quite a lot, namely the high interest of participants, the community who are very supportive, and abundant natural resources.